Analisis Faktor-Faktor yang Mempengaruhi Keputusan Nelayan Tinggal di Permukiman Air Laut di Kelurahan Hajoran Kecamatan Pandan Kabupaten Tapanuli Tengah - Siti Khairani Jamal Saragih; Mahara Sintong (Asosiasi Dosen Muda Indonesia, 2026)
Sea-water settlements are residential areas for fishing communities characterized by unique environmental conditions, limited infrastructure, inadequate sanitation, and high exposure to coastal hazards. Despite these challenges, most residents continue to live in these settlements. This study aims to analyze the characteristics of sea-water settlements, the factors influencing fishermen’s decisions to remain in these settlements, the adaptation strategies adopted to cope with disaster risks, and the future residential plans of fishermen's families in Hajoran Village, Pandan District, Central Tapanuli Regency. This research employed a mixed methods approach combining quantitative and qualitative methods. Quantitative data were collected through questionnaires administered to 133 fishermen households, while qualitative data were obtained through interviews, observations, and documentation. The results indicate that the characteristics of the settlement represent a form of adaptation to the coastal environment and fishing activities. Economic factors were found to be the most dominant determinants of residents' decisions to remain, particularly household financial capacity, high relocation costs, and relatively affordable housing prices. The community also adapts by strengthening house structures, adjusting fishing activities according to weather conditions, implementing household economic strategies, maintaining social cooperation, and increasing preparedness for extreme weather. Most residents intend to remain in the settlement while gradually improving their houses according to their financial capacity.